Design, construction and characterisation of a low-level radioactivity counting system based on gamma-ray spectrometry with LaBr3:Ce scintillator detectors - Bashir, Munirat (Stellenbosch : Stellenbosch University., 2020)
Thesis (PhD)--Stellenbosch University, 2020.